The Influence of Management Discussion and Analysis (MD&A) on Investor Reactions - Reza, Muhammad; Dahlan, Muhammad; Rahman, Syaiful (Eduvest - Journal of Universal Studies, 2025)
This research aims to provide empirical evidence of investor reactions to the disclosure of Management's Discussion and Analysis (MD&A) and Trading Volume Activity (TVA) for companies listed on the Indonesia Stock Exchange from 2015 to 2021. The motivation for this study is the lack of research in Indonesia examining the impact of MD&A on investor decisions, as illustrated by market reactions to stock returns and trading volume activity (TVA). The data used in this research is secondary data obtained from the Annual Reports of companies listed on the Indonesia Stock Exchange (IDX), Refinitiv ESG (Environmental, Social, and Governance) data, and the list of Historical Prices from Yahoo Finance for the period 2015-2021. This study includes 259 data points from 37 companies over the period 2015-2021. Hypothesis testing is conducted using multiple linear regression and non-parametric partial correlation tests. The results indicate that (1) there is no significant positive relationship between MD&A disclosures and stock returns, but (2) there is a significant positive effect of MD&A disclosures on trading volume activity (TVA). This study also incorporates a paired sample t-test to identify differences in stock prices and TVA before and after the disclosure. Implementing these strategies can enhance the productivity and performance of healthcare institutions.